Synthesis, Activity, Toxicity, and In Silico Studies of New Antimycobacterial N-Alkyl Nitrobenzamides - João P. Pais; Olha Antoniuk; David Pires; Tiago Delgado; Andreia Fortuna; Paulo J. Costa; Elsa Anes; Luis Constantino (MDPI AG, 2024)
Tuberculosis (TB) is a disease that plagues the frailest members of society. We have developed a family of N-alkyl nitrobenzamides that exhibit promising antitubercular activities and can be considered a structural simplification of known inhibitors of decaprenylphosphoryl-β-D-ribofuranose 2'-oxidase (DprE1), an essential Mycobacterium tuberculosis (Mtb) enzyme and an emergent antitubercular target. Hereby, we report the development of these compounds via a simple synthetic methodology as well as their stability, cytotoxicity, and antitubercular activity. Studying their in vitro activity revealed that the 3,5-dinitro and the 3-nitro-5-trifluoromethyl derivatives were the most active, and within these, the derivatives with intermediate lipophilicities presented the best activities (MIC of 16 ng/mL). Additionally, in an ex vivo macrophage model of infection, the derivatives with chain lengths of six and twelve carbon atoms presented the best results, exhibiting activity profiles comparable to isoniazid. Although the proof is not definite, the assessment of susceptibility over multiple mycobacterial species, together with the structure similarities with known inhibitors of this enzyme, support DprE1 as a likely target of action for the compounds. This idea is also reinforced by the docking studies, where the fit of our more active compounds to the DprE1 binding pocket is very similar to what was observed for known inhibitors like DNB1.